RETRACTED: Does Green Financing Develop a Cleaner Environment for Environmental Sustainability: Empirical Insights From Association of Southeast Asian Nations Economies - Fu, Weiwei; Irfan, Muhammad (Frontiers in Psychology, 2022)
One of the most frequently used terms in climate change discussions is environmental sustainability. With economic growth and foreign direct investment as moderator factors, this study investigates the influence of green finance and financial development on environmental sustainability and growth in ASEAN economies from 2012 to 2019. ADF and Phillip-Peron (PP) unit root tests, fully modified least square (FMOLS), were employed for long-run empirical estimates. A substantial body of evidence supports the study's findings using VECM technology. Green financing was negatively associated with CO2 emissions. However, environmental sustainability in ASEAN is favorably associated with green financing. It is also worth noting that green financing promotes environmental sustainability at the expenditure of economic growth. Financial development, foreign direct investment, R&D investment, and green technology foster economic expansion at the price of environmental sustainability. There are still many fences to green finance that need to be addressed, including pricing CO2 emissions and reforming inefficient nonrenewable fossil fuel subsidies. Local governments play a vital role in eliminating these barriers and addressing disincentives. It is recommended that policymakers push the financial sector to adopt a green finance strategy to further the goals of long-term sustainable development. Industry must integrate multiple objectives, such as inclusive growth and environmental protection and productivity, through an even broader range of legislative frameworks ideal for decoupling growth from social and ecological unsustainability, at the heart of the green manufacturing process.